Effects of acute multinutrient supplementation on rugby union game performance and recovery - Minett, G.; Duffield, R.; Bird, S. (International Journal of Sports Physiology and Performance, 2010)
Purpose: To investigate the effects of an acute multinutrient supplement on game-based running performance, peak power output, anaerobic by-products, hormonal profiles, markers of muscle damage, and perceived muscular soreness before, immediately after, and 24 h following competitive rugby union games. Methods: Twelve male rugby union players ingested either a comprehensive multinutrient supplement (SUPP), [RE-ACTIVATE:01], or a placebo (PL) for 5 d. Participants then performed a competitive rugby union game (with global positioning system tracking), with associated blood draws and vertical jump assessments pre, immediately post and 24 h following competition. Results: SUPP ingestion resulted in moderate to large effects for augmented 1st half very high intensity running (VHIR) mean speed (5.9 ± 0.4 vs 4.8 ± 2.3 m/min; d = 0.93). Further, moderate increases in 2nd half VHIR distance (137 ± 119 vs 83 ± 89 m; d = 0.73) and VHIR mean speed (5.9 ± 0.6 v 5.3 ± 1.7 m/min; d = 0.56) in SUPP condition were also apparent. Postgame aspartate aminotransferase (AST; 44.1 ± 11.8 vs 37.0 ± 3.2 UL; d = 1.16) and creatine kinase (CK; 882 ± 472 vs. 645 ± 123 UL; d = 0.97) measures demonstrated increased values in the SUPP condition, while AST and CK values correlated with 2nd half VHIR distance (r = -0.71 and r = -0.76 respectively). Elevated C-reactive protein (CRP) was observed postgame in both conditions; however, it was significantly blunted with SUPP (P = .05). Conclusions: These findings suggest SUPP may assist in the maintenance of VHIR during rugby union games, possibly via the buffering qualities of SUPP ingredients. However, correlations between increased work completed at very high intensities and muscular degradation in SUPP conditions, may mask any anticatabolic properties of the supplement.